(3GdMUGQ aj GdMSGHs - (3eMeO Hf YHO Gddg Hf eMeO Hf YjGT, GdMUGQs ((3GSjhW s)
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI GdMeO ddg GdPj de jJNP UGMHI hdG hdOkG CeG HYO CdgefG Gddg aCdaJ aj GdYOO gPG GdJCdja hfHgJ ajg Ydi cd eYfj aaj dWja djchf JHUQI ddegfOjf s
(3BNQgG (B:s
(3aEf bGd ce MPQ KdGKI CSHGY aCVQHI dCfg CSHGY aj YOO eQHY dg SHY hPdc JSYI hGQHYhf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
Keywords: (3GdQjGVjGJs